Diagnosis, Treatment, Follow-up, and Persistence of Trichomonas vaginalis in Women 45 Years and Older According to HIV Status: A 10-Year Retrospective Cohort. Issue 5 (May 2020) - Lazenby, Gweneth B.; Hill, Allyson; Tarleton, Jessica; Soper, David
Abstract : Background: Trichomonas vaginalis is a common treatable sexually transmitted infection among older women. Persistent T. vaginalis infection after treatment is common among women with human immunodeficiency virus (HIV). We sought to determine if HIV-negative women were as likely as women with HIV to have persistent T. vaginalis infection. Methods: We performed a retrospective cohort study of women 45 years or older with T. vaginalis infection. We evaluated differences in persistent T. vaginalis infection according to HIV status using χ 2 analysis. We performed regression analyses to describe factors associated with persistent and recurrent infection in older women. Results: Over a 10-year study period, we identified 282 women with T. vaginalis, 46 with HIV. Most women (240, 86%) were treated in accordance with 2015 Centers for Disease Control and Prevention Sexually Transmitted Diseases treatment guidelines. Half of the women (144, 53%) had a repeat T. vaginalis test 90 to 365 days after treatment, and one third had persistent infection (39/125, 31%). Persistent infection was similar between women with HIV and HIV-negative women treated according to Centers for Disease Control recommendations (17% vs 33%, P = 0.3). When adjusting for age and incidental diagnosis, tobacco use was associated with an increased risk of more than 1 or recurrent T. vaginalis infection during the study period (adjusted odds ratio, 2.8; 95% confidence interval, 1.5–4.9). Conclusions: The HIV status did not affect persistent T. vaginalis infection in women 45 years or older. Given over one third of women have a positive test within a year after the recommended treatment, our data support repeat testing in women 45 years and older treated for T. vaginalis . Abstract : Persistent Trichomonas vaginalis infection is common among women 45 years and older. Human immunodeficiency virus status was not associated with persistent or recurrent infection. More effective treatment strategies are needed.